PRIMARY SCHOOL ENGINEERING TECHNIQUES TO INCLUDE STUDENTS TO READ THROUGH DIDACTIC GAMES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
About the use of didactic games in the development of the effectiveness of education in primary school, the educational and practical significance of the subject, to stimulate students' interest in learning the subject.